LITERATURE REVIEW : PEMBERDAYAAN KESEHATAN MASYARAKAT PESISIR MELALUI TANAMAN MANGROVE - Arini Fajriani; Susilawati Susilawati (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2023)
Community empowerment can be understood as an endeavor to restore or increase a group's capability so that they can exercise their rights and obligations as community members in a dignified manner. Mangroves are seen by residents of coastal communities as playing a significant role in the environment. Mangroves are a very promising plant because each portion may be utilized to make traditional remedies, in addition to protecting land from sea waves. The purpose of this study was to determine the function of mangrove plants as a health empowerment for coastal communities. The methodology used in this research is Systematic Literature Review (SLR). The data used in the research was sourced from the Google Scholar publication database, Neliti and Research Gate using the keywords